Late-Life Depressive Symptomatology, Motoric Cognitive Risk Syndrome, and Incident Dementia: The “NuAge” Study Results - Beauchet, Olivier; Sekhon, Harmehr; Launay, Cyrille P.; Gaudreau, Pierrette; Morais, José A.; Allali, Gilles (Frontiers in Aging Neuroscience, 2021)
Background. Late-life depressive symptomatology and motoric cognitive risk (MCR) have independently been associated with an increased risk for incident dementia. This study aims to examine the association of late-life depressive symptomatology, MCR and their combination on incident dementia in community-dwelling older adults living in Quebec (Canada). Methods. The study was carried out in a subset of 1,098 community-dwellers aged >65 recruited in the “Nutrition as a determinant of successful aging: The Quebec longitudinal study” (NuAge), an observational prospective cohort study with 3 years follow-up. At baseline, MCR was defined by the association of subjective cognitive complaint with slow walking speed, and late-life depressive symptomatology with a 30-item Geriatric Depression Scale (GDS) score >5/30. Incident dementia, defined as a Modified Mini-Mental State score ≤79/100 test and Instrumental Activity Daily Living score <4/4, was assessed at each annual visit. Results. The prevalence of late-life depressive symptomatology only was 31.1%, of MCR only 1.8% and the combination of late-life depressive symptomatology and MCR 2.4 %. The combination of late-life depressive symptomatology and MCR at baseline was associated with significant overall incident dementia (Odd Ratio (OR)=2.31 with P<0.001) but not for MCR only (OR=3.75 with P=0.186) or late-life depressive symptomatology only (OR=1.29 with P=0.276). Conclusions. The combination of late-life depressive symptomatology and MCR is associated with incident dementia in older community-dwellers. The results suggest an interplay between late-life depressive symptomatology and MCR exposing to an increased risk for dementia.